2016
DOI: 10.1142/s2010135x1630005x
|View full text |Cite
|
Sign up to set email alerts
|

Voltage control of ferromagnetic resonance

Abstract: Voltage control of magnetism in multiferroics, where the ferromagnetism and ferroelectricity are simultaneously exhibiting, is of great importance to achieve compact, fast and energy efficient voltage controllable magnetic/microwave devices. Particularly, these devices are widely used in radar, aircraft, cell phones and satellites, where volume, response time and energy consumption is critical. Researchers realized electric field tuning of magnetic properties like magnetization, magnetic anisotropy and permeab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 75 publications
(128 reference statements)
0
6
0
Order By: Relevance
“…In addition, the ferroelectric TTB-Eu layer filling the space between the magnetic BaFO nanorods increases the area of the interface between the two layers. This does enhance the interfacial interactions between the two components of this multiferroic composite system, enhancing the magnetoelectric coupling [ 50 , 51 , 52 ] between the ferroelectric (TTB-Eu) and the magnetic (BaFO) components.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the ferroelectric TTB-Eu layer filling the space between the magnetic BaFO nanorods increases the area of the interface between the two layers. This does enhance the interfacial interactions between the two components of this multiferroic composite system, enhancing the magnetoelectric coupling [ 50 , 51 , 52 ] between the ferroelectric (TTB-Eu) and the magnetic (BaFO) components.…”
Section: Resultsmentioning
confidence: 99%
“…[9] Numerous research achievements have been reported on voltage tuning of FMR involving various geometries and materials. [9,[32][33][34][35][36] Voltage control of magnetism may facilitate wide FMR modification in an energy efficient way for application in voltage-tunable spintronic devices. [37]…”
Section: Voltage Tuning Of Ferromagnetic Resonancementioning
confidence: 99%
“…[44] Nevertheless, the FMR measurements were often accompanied by a large FMR linewidth from the magnetic phase, which limits the practical application. [35,45] In order to reduce the FMR linewidth while maintaining giant electrical modulation, Liu et al reported on a novel amorphous FeGaB film as a magnetic layer that retained strong absorption over a small linewidth of approximatively 50 Oe, [22] while preserving PZN-PT(011) as the piezoelectric substrate. [46] The 50-nm-thick FeGaB film was deposited onto PZN-PT(011) substrates utilizing co-sputtering of Fe 80 Ga 20 and B targets.…”
Section: Voltage Control Of Fmr Via Strain/stressmentioning
confidence: 99%
“…Electric field instead of the conventional current trigger can not only reduce the energy consumption but also increase the efficiency of functional devices. These features greatly expand the application range of magnetic materials and demonstrate its broad application in the field of new magnetoelectric storage devices, ,, microwave devices, and logic circuits. Therefore, great efforts have been dedicated to achieving converse ME coupling via voltage modulated magnetization without the external magnetic field and study the mechanisms of this coupling in piezoelectric/ferromagnetic heterostructures at room temperature. The purpose of this article is to realize a purely electric field control of magnetism variation in LSMO/PMN–PT multiferroic heterostructures by means of the room-temperature MOKE measurement, which possesses a very high precision, in situ, and nondestructive test. This work presents the change of magnetic hysteric loops under different DC voltages.…”
Section: Introductionmentioning
confidence: 99%